2018
DOI: 10.3390/foods7020025
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Rheological Properties of a Dairy Dessert, Enriched with Chickpea Flour

Abstract: Dairy desserts are complex mixtures and matrices including main components such as milk, sugar, starch, hydrocolloids, colorants and flavors, with a proteinaceous structure; they are widely consumed and present a semisolid consistency. In this work, the physicochemical and rheological properties of a dairy dessert with the addition of chickpea flour (raw and cooked, at four concentrations) were studied to determine the effect of the flour. The results indicated that luminosity (L*: 62.75–83.29), pH (6.35–7.11)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
4
17
1
Order By: Relevance
“…where σ 0, K, and n represent yield stress (Pa), consistency coefficient (Pa.s) and flow behavior index (n), respectively …”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…where σ 0, K, and n represent yield stress (Pa), consistency coefficient (Pa.s) and flow behavior index (n), respectively …”
Section: Methodssupporting
confidence: 72%
“…This trend most likely reflects higher starch content of FMCCo (Table ). Previous studies have reported a positive correlation between the starch content and viscosity of heated starch‐based suspensions . Nevertheless, the differences in σ 0, K and η 120s‐1 between R‐FMCCo and R‐FMCCw suggest that viscosity are also likely to be influenced by the interactive effects of other parameters, apart from flow behavior index, such as differences in FMCC composition (including lactic acid, fat, and β ‐glucan; Table ) and granular structure .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The changes in shear stress ( σ ; Pa) and viscosity ( η ; Pa.s) were recorded. The resultant σ versus trueγ˙ data were fitted to the Herschel–Bulkley model using TA data analysis software (TA Rheology Advance Data Analysis, Version V5.7.0):σ=σ0+Ktrueγ˙nwhere σ 0 , K , and n represent yield stress (Pa), consistency coefficient (Pa.s), and flow behavior index ( n ), respectively (Aguilar‐Raymundo & Vélez‐Ruiz, ).…”
Section: Methodsmentioning
confidence: 99%
“…These dairy beverages are formulated with ingredients such as milk, sucrose, cocoa powder and some hydrocolloids that are added to improve consistency [11]. Aguilar-Raymundo and Vélez-Ruiz [12] reported that the storage modulus was larger than the loss modulus in a milk-based dessert, which is characteristic of viscoelastic materials such as dispersions and gels. The elastic response dominated the viscose, resulting in a gelatinous response.…”
Section: Resultsmentioning
confidence: 99%